Pericardial effusion in an Indian context: clinical insights and dynamics from a tertiary care centre - Nafeez Javed Shaik; Sindhu Sujeeth Hegde; Shubha Seshadri; Mounika Cherukuri (BMC Cardiovascular Disorders)
Abstract Background Pericardial effusion (PE) indicates the build-up of fluid within the pericardial sac, which encases the heart. The present study was undertaken to assess the clinical profile, etiology of pericardial effusion and to determine the correlation of cardiac tamponade and constrictive pericarditis with etiology. Methods A prospective observational hospital based longitudinal study was undertaken among the 88 newly diagnosed and known patients of pericardial effusion who are above 18 years. The clinical profile of pericardial effusion including history, examination, standard lab parameters routinely done including thyroid function tests, HIV Serology, ECG, Echocardiography and imaging if done (HRCT thorax), pericardial fluid analysis (if performed) were elicited. Results Majority of the patients were males (55.7%), with a mean age of 51.3 years. Among the 88 patients of pericardial effusion, 20 had cardiac tamponade, 13 individuals were diagnosed with constrictive pericarditis. Dyspnea was the most common presenting complaint (65.9%). Chronic kidney disease / uremia is the most common cause of pericardial effusion accounting for 25%, followed by neoplastic (20.5%) and tuberculosis (17%). While in cardiac tamponade patients neoplasm followed by tuberculosis were the most common etiology, patients with constrictive pericarditis had tuberculosis followed by chronic kidney disease as the most common etiology. Echocardiography features were not significantly different according to the etiology of the pericardial effusion (p > 0.05). Thickened pericardium found in the echocardiography showed maximum specificity (76.9%), while thickened fluid/exudates showed maximum sensitivity (65.2%) and negative predictive value (77.1%) for tuberculous pericardial effusion. Conclusion Chronic kidney disease, closely followed by infections (mostly tuberculosis), are the frequent causes of PE in the present settings. Breathlessness is the most frequent clinical feature in the patients of PE. Fibrin strands, thickened pericardium, thickened fluid in Echocardiography assists in diagnosing tubercular pericardial effusion. Cardiomegaly in chest X-ray or CT scans should further prompt towards diagnosing pericardial effusion. It is essential to incorporate these findings into the clinical practice, by evaluating the patients presenting with breathlessness for PE. CKD needs to be placed on par with tuberculosis while suspecting the etiology of the PE in the present settings. ADA levels in pericardial fluid (> 40) can be considered as a specific marker for tubercular PE.